- Semiotics Analysis Method in Architectural Research: - - Handoko, Jarwa Prasetya Sih (Talenta Publisher, 2024)
Semiotics is the study of signs in the social life of society. While architectural semiotics is a method of analysis in architectural research that views an architectural work as a collection of signs that become a marker to convey a sign of meaning or message to its users. The objective of this study is to establish the scope of the use of semiotic analysis methods in architectural studies in terms of the variety of research topics and findings that can be obtained from these studies. This study is a descriptive exploratory study with a literature study related to the use of semiotic analysis methods in research in the field of architecture. From the results of the study note that the semiotic analysis method can be used to examine the meaning or message both visual and non-visual that exists in architectural works. There are markers and markers in the form of architecture that describe the culture of the local community. The search for meaning or message contained in an architectural work can be carried out with several semiotic analysis strategies.